STUDI LOYALITAS KARYAWAN DENGAN KEPEMIMPINAN DAN KEPUASAN KERJA SEBAGAI PREDIKTOR DI SEBUAH RUMAH SAKIT SWASTA DI KABUPATEN SEMARANG - Taufik Hidayat; Andhi Supriyadi; Bambang Guritno; Sapto Supriyanto (LPSDI Bina Patria, 2024)
Employee loyalty is an employee's feeling of loyalty or knowledge of their company which can be seen from their work discipline, responsibility and behavior while working at the company. Employees who have loyalty will display a positive attitude and follow the rules determined by the company. Many factors can influence employee loyalty such as leadership and job satisfaction. Therefore, the aim of this research is to determine the influence of leadership and job satisfaction on employee loyalty. The research population was employees of private hospitals in Semarang Regency with a sample of 90 employees as respondents. The sampling technique in this research was a simple random technique. The analysis technique used is multiple regression with instrument testing (validity and reliability) previously carried out. The research results show: Leadership has a positive effect on employee loyalty. Job Satisfaction has a positive effect on Employee Loyalty. Leadership and Job Satisfaction together have a positive effect on Employee Loyalty